Social and economic variables associated with academic achievement - Al - Qurashi, Awad bin Mohammed (Journal of Humanities & Social Sciences, 2019)
The study seeks to identify the relationship between the social and economic variables associated with academic achievement. Under this main goal are three sub goals: 1.The level of performance.2.Distribution to academic departments.3.Joining the "talent" system. The study based on the quantitative approach using a field survey method on a random sample of 422 students. The most important results are: One of the most influential social factors related to academic achievement (for the sample of the study) is in descending order: 1.The educational level of the mother where the correlation coefficient was 0.508 at the level of significance (0.01). 2.The educational level of the father where the ratio of correlation was 0.416 at the level of significance (0.01). 3.The extent of the effect of the parents in the choice of specialization, where the value of correlation coefficient 0.329 at the level of significance (0.01). 4.The degree of parental interest in presenting cultural programs where the correlation coefficient was 0.297 at the level of (0.01). One of the most influential economic factors associated with the achievement of the study (for the sample of the survey) is in descending order: 1.The work of the father where the coefficient of correlation 0.408 at the level of significance (0.01). 2.The monthly income of the family where the ratio of the relationship was 0.349 at the level of significance (0.01). 3.The presence of brothers who have jobs to the student where the coefficient of correlation 0.318 at the level of significance (0.01). 4.Housing ownership with a correlation coefficient of 0.280 at a concentration of significance (0.01).